2020
DOI: 10.14738/abr.712.7560
|View full text |Cite
|
Sign up to set email alerts
|

The THE EFFECTS OF LOCAL CULTURE ON TOURISM PRODUCTS AND DOMESTIC TOURIST SATISFACTION IN TOURISM DESTINATIONS

Abstract: The beauty of nature, the uniqueness of the culture and the hospitality of its inhabitants put the island of Bali first in the world, beating the Maldives and Phuket, Thailand. Bali ranks first among the 25 best destinations in the world (Trip Adivisor, 2017). The purpose of this study is to prove and analyze the influence of local culture on tourism products and the satisfaction of domestic tourists at tourist destinations in Gianyar regency of Bali province. The population in this study is domestic tourists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Virtual reality technology is to put the user into the virtual environment completely and realize the interaction with the electronic system using the natural perception of humans. Explicitly, with the own visual, auditory, tactile, and other senses of human beings, the user can get the same feeling of the visual, auditory, tactile, and other stimuli provided by the system in the system as in the real world (Bagus et al, 2020 ; Szczsna and Wesoowska, 2020 ).…”
Section: Vr Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual reality technology is to put the user into the virtual environment completely and realize the interaction with the electronic system using the natural perception of humans. Explicitly, with the own visual, auditory, tactile, and other senses of human beings, the user can get the same feeling of the visual, auditory, tactile, and other stimuli provided by the system in the system as in the real world (Bagus et al, 2020 ; Szczsna and Wesoowska, 2020 ).…”
Section: Vr Methodsmentioning
confidence: 99%
“…The VR technology is applied to digital tourism technology to realize the VR of tourism products. Bagus et al believe that the concept of wireless augmented VR has recently swept the entire 5G ecosystem, causing unprecedented interest in academia, industry and other fields (Bagus et al, 2020 ). However, the success of the VR experience in the present situation depends on solving a large number of major challenges across multiple disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from prior research indicate that, overall, tourist satisfaction is influenced by tourism products (Bagus et al, 2020;Siregar et al, 2021) service quality at tourist destinations, as well as experiences encountered when tourists participate in activities. The results of the study from Back et al (2021) suggested that tourist experience satisfaction has a positive and significant influence on revisit intention, and this will be strong if the guide's performance is good.…”
Section: Tourist Satisfaction As Mediating Variablementioning
confidence: 99%
“…Kuatnya budaya lokal tesebut dapat menjadi ciri tersendiri pada sebuah masyarakat. Budaya lokal menjadi pembeda satu masyarakat dengan masyarakat lainnya (Aisara et al, 2020;Aref et al, 2010;Cempena et al, 2019). Bahkan dalam konteks Indonesia, masyarakat dalam satu wilayahpun dapat memiliki kebudayaan lokal (local genius) yang berbeda-beda.…”
Section: Pendahuluanunclassified